2015
DOI: 10.1104/pp.15.00107
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Wheat with the Green Leaf Volatile Z-3-Hexenyl Acetate Enhances Defense against Fusarium graminearum But Boosts Deoxynivalenol Production

Abstract: Priming refers to a mechanism whereby plants are sensitized to respond faster and/or more strongly to future pathogen attack. Here, we demonstrate that preexposure to the green leaf volatile Z-3-hexenyl acetate (Z-3-HAC) primed wheat (Triticum aestivum) for enhanced defense against subsequent infection with the hemibiotrophic fungus Fusarium graminearum. Bioassays showed that, after priming with Z-3-HAC, wheat ears accumulated up to 40% fewer necrotic spikelets. Furthermore, leaves of seedlings showed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
117
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(129 citation statements)
references
References 75 publications
(105 reference statements)
8
117
1
Order By: Relevance
“…Primed wheat plants with the GLV Z-3-hexenyl acetate (Z-3-HAC) showed reduced fungal spread in subsequent F. graminearum infections, although accumulated higher levels of mycotoxins (Ameye et al, 2015). Moreover Z-3-HAC was responsible for the transition from SA-to JA-dependent defences, occurring at 2 dpi (Ameye et al, 2015). This study showed that wounding (mock-inoculation) triggered genes for GLV production, including…”
Section: Regulation Of Genes For the Biosynthesis Of Green Leaf Volatmentioning
confidence: 89%
See 2 more Smart Citations
“…Primed wheat plants with the GLV Z-3-hexenyl acetate (Z-3-HAC) showed reduced fungal spread in subsequent F. graminearum infections, although accumulated higher levels of mycotoxins (Ameye et al, 2015). Moreover Z-3-HAC was responsible for the transition from SA-to JA-dependent defences, occurring at 2 dpi (Ameye et al, 2015). This study showed that wounding (mock-inoculation) triggered genes for GLV production, including…”
Section: Regulation Of Genes For the Biosynthesis Of Green Leaf Volatmentioning
confidence: 89%
“…GLV role in priming, which refers to a sensitization of plants to respond faster and/or more strongly to future herbivore insect attack, was demonstrated in maize (Engelberth et al, 2004), but recently also in wheat against fungal pathogens (Ameye et al, 2015). Primed wheat plants with the GLV Z-3-hexenyl acetate (Z-3-HAC) showed reduced fungal spread in subsequent F. graminearum infections, although accumulated higher levels of mycotoxins (Ameye et al, 2015). Moreover Z-3-HAC was responsible for the transition from SA-to JA-dependent defences, occurring at 2 dpi (Ameye et al, 2015).…”
Section: Regulation Of Genes For the Biosynthesis Of Green Leaf Volatmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors demonstrated induction of a suite of defence gene transcripts and proteins in wheat seedlings. Through a priming experiment that enhanced plant defence against F. graminearum in wheat, DON production has also been shown to be boosted [14]. Thus, the effects of DON appear to be complex and the mechanism of toxicity remains poorly understood in plant.…”
Section: Introductionmentioning
confidence: 97%
“…Apart from the hyperstimulation of PTI, necrotrophic fungi typically rely on the production of mycotoxins to induce host necrosis (Christensen and Kolomiets, 2011;Woloshuk and Shim, 2013;Ameye et al, 2015). Future research is required to verify whether the necrotrophic behavior of droplet-inoculated P. cucumerina depends on mycotoxin production and whether such mycotoxin production is stimulated by early immune responses of the host plant.…”
mentioning
confidence: 99%